Rahmah El Yunusiyah: Konsep Pendidikan Agama Islam dan Relevansinya di Abad-21 - M. Afiqul Adib (AL-FIKRA, 2022)
The purpose of this study is to elaborate Rahmah El-Yunusiyyah's thoughts on the concept of Islamic religious education with the times, so as to bring up concepts that are appropriate and relevant to the needs of the 21st century. This literature review uses theoretical philosophical analysis to achieve this goal. The data collection method uses documentation, both primary data and secondary data. While descriptive analysis is the method used for data analysis, the aim is to be able to describe the facts found systematically. and factual way. The data is then processed and analyzed objectively and systematically according to existing procedures. The results of this study found that the perspective of Rahmah El Yunusiyah's Islamic Religious Education is an effort to educate both men and women to always study Islamic religious material from childhood, to lifelong accompanied by professional teachers, role models, and in accordance with time in an effort to fix the problems faced. Then the relevance of Rahmah El Yunusiyyah's thoughts to the 21st century lies in the concept of scientific transformation that he initiated and connectedness with society. This is very important to face the current of globalization which requires a lot of skills, especially in terms of connectivity. Rahmah El Yunusiyah's thoughts on education deserve to be appreciated and explored further.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//